U.S. nursing home leadership experiences with COVID-19 and its impact on residents and staff: A qualitative analysis. - Catherine E Dubé; Natalia Nielsen; Emily McPhillips; J Lee Hargraves; Carol Cosenza; Bill Jesdale; Kate L Lapane (PLoS ONE, 2023)
Objectives To explore experiences of U.S. (United States) nursing home leadership during the COVID-19 pandemic in their efforts to address resident loneliness and social isolation and to elicit stories about personal and professional impacts on themselves and staff. Design Qualitative inquiry via three optional open-ended questions appended to a national self-administered survey of American nursing home leaders was employed. Textual data was analyzed using an iterative reflexive thematic approach. Setting and participants A stratified sample frame defined by facility size (beds: 30-99, 100+) and quality ratings (1, 2-4, 5) was employed. Web survey links and paper surveys were sent to 1,676 nursing home directors of nursing between February and May 2022. Results Open text responses were collected from 271 nursing homes. Broad themes included: 1) Addressing needs of residents & families; 2) Challenges; and 3) Personal experiences of nursing home leadership/staff. Respondents described trauma to residents, staff, and leadership. Resident loneliness was addressed using existing and newer technologies and innovative indoor and outdoor activities. Residents experienced fear, illness, loss, and sometimes death. Isolation from family and lack of touch were particularly difficult. Regulations were seen as punitive while ignoring emotional needs of residents. Staffing challenges and pressures to do more with less created additional stress. Leadership and staff made significant sacrifices resulting in physical, social, and emotional consequences. Beneficial outcomes included staff bonding, professional growth, and permanent implementation of new interventions. Conclusions and implications New and creative interventions were successfully implemented to address social isolation and loneliness. Improved Wi-Fi and other nursing home infrastructure upgrades are needed to maintain them. Reimagining often conflicting overlapping federal, state, and local regulations, grounding them in good clinical judgement, and incentivizing performance improvement should be considered. Trauma experienced by staff needs to be addressed to deal with current and future workforce needs.